Kolaborasi Organisasi Kepemudaan dengan Pengurus Masjid dalam Membentuk Generasi Islami (Studi Pada Kampung Karang Tangah, Kab. Pesisir Selatan) - Putra, Ahmad (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2024)
This research discusses collaboration between youth organizations and mosques and is supported by migrants. This collaboration is not just a formality, but this collaboration aims to bring about changes in teenagers and young people so that they become a useful and moral generation. If this can be realized, an Islamic generation will be born which will certainly continue the struggle of Islam in spreading goodness and things that are useful to many people. For this reason, youth and mosque administrators in Karang Tangah Village, Lengayang District, Pesisir Selatan Regency, West Sumatra have agreed to involve the younger generation in the activities being held in the hope that they will get used to being active in positive activities while also minimizing their influence and behavior. bad things they could have done. This research uses qualitative methods, complemented by observations and interviews. The results of this research, it was found that; firstly, the younger generation is assigned to be active on Ramadan nights such as hosting Ramadan study events, secondly, the younger generation is involved as a committee member in religious events such as being on the MTQ competition committee, funeral prayers, and so on, thirdly, the younger generation is invited to attend meetings -youth meetings held at mosques by youth and mosque officials, fourth, the young generation is involved in social activities, such as collecting donations when there is misfortune and mutual cooperation.Key Word: Youth, Mosques, Next GenerationABSTRAKPenelitian ini membahas mengenai kolaborasi antara organisasi kepemudaan dengan Masjid serta didukung oleh para perantau. Kolaborasi ini berjalan bukan sekedar sebatas formalitas saja, akan tetapi kolaborasi ini bertujuan untuk melahirkan perubahan dari para remaja dan pemuda agar menjadi generasi yang bermanfaat dan berakhlak. Jika hal ini dapat terwujud, maka akan lahir generasi Islami yang tentunya akan meneruskan perjuangan Islam dalam menebar kebaikan dan hal-hal yang bermanfaat untuk banyak orang. Oleh sebab itu, pemuda dan pengurus Masjid di Kampung Karang Tangah, Kecamatan Lengayang, Kabupaten Pesisir Selatan, Sumatera Barat bersepakat melibatkan para generasi muda pada kegiatan-kegiatan yang diselenggarakan dengan harapan mereka terbiasa aktif pada kegiatan yang positif sembari di samping itu meminimalisir pengaruh dan perilaku buruk yang bisa saja mereka lakukan. Penelitian ini menggunakan metode kualitatif, dengan dilengkapi dengan dilakukannya observasi dan wawancara. Hasil dari penelitian ini, ditemukan bahwa; pertama, generasi muda ditugaskan untuk aktif di malam-malam ramadhan seperti menjadi pembawa acara kajian ramadhan, kedua, generasi muda dilibatkan sebagai panitia dalam acara keagamaan seperti menjadi panitia lomba MTQ, shalat jenazah, dan lain sebagainya, ketiga, generasi muda diundang untuk menghadiri rapat-rapat kepemudaan yang diadakan di masjid oleh perangkat kepemudaan dan masjid, keempat, generasi muda dilibatkan dalam kegiatan sosial, seperti mengumpulkan donasi ketika ada kemalangan dan gotong royong.Kata Kunci: Pemuda, Masjid, Generasi Penerus